2004
DOI: 10.1007/s11255-004-0847-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of distigmine bromide in the treatment of patients with underactive detrusor

Abstract: Distigmine bromide shows clinical efficacy in patients with poor detrusor function and may therefore be used alternatively in selected cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 11 publications
0
23
0
1
Order By: Relevance
“…The use of available oral drugs show limited clinical benefits,10, 11 and have numerous undesired side effects 12. Willing and physically able patients can use intermittent self‐catheterization.…”
Section: Introductionmentioning
confidence: 99%
“…The use of available oral drugs show limited clinical benefits,10, 11 and have numerous undesired side effects 12. Willing and physically able patients can use intermittent self‐catheterization.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, distigmine is one of the most important clinical urology therapeutics employed to treat lower urinary tract dysfunction and this compound is used for neurogenic underactive bladder ascribed to surgery, spinal cord injury, and diabetes. [2][3][4][5][6][7][8] It is also effective against drug-and prostate enlargement-induced dysfunctions of urinary excretion.…”
mentioning
confidence: 99%
“…In particular, distigmine is one of the most important clinical urology therapeutics employed to treat lower urinary tract dysfunction and this compound is used for neurogenic underactive bladder ascribed to surgery, spinal cord injury, and diabetes. [2][3][4][5][6][7][8] It is also effective against drug-and prostate enlargement-induced dysfunctions of urinary excretion. [9][10][11][12][13] Distigmine thus plays a significant role as a principal therapeutic for urinary excretion dysfunctions associated with an underactive bladder, whereas new generations of anticholinergic drugs or beta3 adrenoceptor agonists tend to be employed to treat conditions associated with an overactive bladder.…”
mentioning
confidence: 99%
“…1), a reversible and long-acting carbamate cholinesterase inhibitor, has been clinically used to treat patients with voiding dysfunction associated with impaired detrusor contractility. 9-11) Bougas et al 9) reported that treatment with distigmine resulted in a statistically significant reduction in residual volume and percentage residual volume, obviating the need for intermittent selfcatheterization in patients with detrusor underactivity. In addition, the maximum flow rate and detrusor pressure at maximum flow increased.…”
mentioning
confidence: 99%